The effect of corporate culture on firm performance: Evidence from China - Hailin Zhao; Haimeng Teng; Qiang Wu (China Journal of Accounting Research, 2018)
This study examines whether corporate culture promotion affects firm performance in China in terms of firm market value, firm financial performance and innovation output. We find consistent evidence that corporate culture promotion is negatively related to firm market value, positively related to innovation output and not significantly related to firm financial performance. In addition, the negative effect of corporate culture promotion on firm market value is driven by small firms and firms located in less developed provinces. Furthermore, we find that some specific corporate culture promotions, such as innovation culture promotion and integrity culture promotion, are not related to firm value or financial performance. However, innovation culture promotion is positively associated with innovation output.
Keywords: 650; Corporate culture promotion; Firm performance; China